AOBA VELOX-IV: 2U CubeSat for the technological demonstration of lunar horizon glow mission. (August 2019) - Kim, Sangkyun; Orger, Necmi Cihan; Cordova-Alarcon, Jose Rodrigo; Hernandez-Herrera, Marcos; Masui, Hirokazu; Yamauchi, Takashi; Toyoda, Kazuhiro; Cho, Mengu; Duy Vu, Bui Tran; Vinh, Tran Quang; Seng, Lim Wee; Hiang, Cheng Tee
Abstract: AOBA VELOX-IV is a 2U-sized CubeSat that has been developed by the Kyushu Institute of Technology and Nanyang Technological University for the technological demonstration of a future lunar mission. Decades ago, Surveyor and Apollo programs reported light scattering observations on the horizon of the Moon; however, only a limited number of investigations were performed after the Apollo program to observe the lunar horizon glow (LHG). It is still unknown what conditions produce the light glow on the horizon of the Moon. The lunar mission of the AOBA VELOX project is planning to send CubeSats to the Moon and to capture images of the LHG on the lunar orbit while determining the conditions that can support light scattering above the lunar horizon. Before the satellites go into the lunar orbit, the necessary technologies must first be confirmed in Earth orbit. AOBA VELOX-IV was launched to low earth orbit via a JAXA Epsilon rocket in 18th January 2019. This paper explains the LHG mission first, and presents an overview of AOBA VELOX-IV, its payloads, technical issues, and the flight model. Highlights: LHG(Lunar Horizon Glow) was reported from the era of Apollo missions. Small satellites increase the chance of observations. The necessary technologies need to be confirmed first. AOBA VELOX-IV is 2U size CubeSat for the technology demonstration. The satellite is ready, and will test its missions on Earth orbit.